2023
DOI: 10.1101/2023.03.11.531013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Switch-like Compaction of Poly(ADP-ribose) Upon Cation Binding

Abstract: Poly(ADP-ribose) (PAR) is a homopolymer of adenosine diphosphate ribose that is added to proteins as a post-translational modification to regulate numerous cellular processes. PAR also serves as a scaffold for protein binding in macromolecular complexes, including biomolecular condensates. It remains unclear how PAR achieves specific molecular recognition. Here, we use single-molecule fluorescence resonance energy transfer (smFRET) to evaluate PAR flexibility under different cation conditions. We demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…Previously, we have shown that PAR possesses a larger persistence length than RNA, thereby being stiffer, a characteristic attributed to the greater electrostatic repulsion imposed by two phosphates instead of one in RNA per monomer. 23 Both PAR and RNA assume more compact states with increasing salt concentration—a compaction that occurs with 100x fewer divalent than monovalent ions. 23 Building on this polymeric characterization, we set out to explore the 3D structure of PAR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we have shown that PAR possesses a larger persistence length than RNA, thereby being stiffer, a characteristic attributed to the greater electrostatic repulsion imposed by two phosphates instead of one in RNA per monomer. 23 Both PAR and RNA assume more compact states with increasing salt concentration—a compaction that occurs with 100x fewer divalent than monovalent ions. 23 Building on this polymeric characterization, we set out to explore the 3D structure of PAR.…”
Section: Discussionmentioning
confidence: 99%
“…23 Both PAR and RNA assume more compact states with increasing salt concentration—a compaction that occurs with 100x fewer divalent than monovalent ions. 23 Building on this polymeric characterization, we set out to explore the 3D structure of PAR. Our studies reveal that the structure of PAR markedly diverges from that of poly-A RNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAR chains are also stiffer than RNA or DNA chains. 30 This section is a primer on the enzymatic cycle underlying PAR synthesis and catabolism, and the catalytic activity of PARPs.…”
Section: Poly(adp-ribose) Structure and Synthesismentioning
confidence: 99%
“…Therefore, the structure of an ADP-ribose unit resembles NAD + without the nicotinamide group. , Target proteins can be mono- or poly­(ADP-ribosylated), and PAR chains can be up to ∼200 units long. , Because PAR chains are covalently attached to proteins, long PAR modifications significantly impact the structure and biochemical properties of the target protein. PAR chains are also stiffer than RNA or DNA chains . This section is a primer on the enzymatic cycle underlying PAR synthesis and catabolism, and the catalytic activity of PARPs.…”
Section: Poly(adp-ribose) Structure and Synthesismentioning
confidence: 99%